Visual Expertise in History: Historians’ and Novices’ Visual Processing and Interpretation of Historical Images - Puurtinen, Marjaana; Kaakinen, Johanna K.; Jarodzka, Halzska (Michigan State University, Department of Psychology, 2026)
Drawing on expertise research and scene perception studies, this study investigates the characteristics of visual expertise in the domain of history by examining historians’ and novices’ visual processing and task performance in an image integration task. Task complexity was manipulated by altering the ease of identifying the topic depicted in a series of historical images. Historians (n = 40) and novices (n = 40) were shown a series of black-and-white images. Their eye movements were recorded, and each participant identified a topic for each series. Their written responses were coded for appropriateness and whether they described the topic as part of a historical process. The results showed that compared to novices, historians exhibited more consistent gaze behavior for each series of images, indicating a systematic approach to interpreting them. Furthermore, novices’ fixation durations increased, and the number of fixations tended to decrease from the first to the final image, suggesting that their gaze became more focused only for the later images. Expertise also affected task performance: In the case of a more challenging set of images, historians provided more appropriate topic answers and interpreted the topics as part of a historical process, indicating that they were able to situate even the more complex series within a meaningful bigger picture. Thus, even in the ill-structured domain of history, domain expertise induces differences in the visual processing and interpretation of domain-related images compared to lack of such expertise.